Appendiceal torsion associated with undescended caecum: a case report and review of the literature. (25th September 2012) - Dimitriadis, Panagiotis A; Makar, Ragai R; Randall, Jon K; Ramus, James
Abstract : Torsion of the vermiform appendix is a rare disorder that causes symptoms similar to those of acute appendicitis. Primary and secondary causes of appendiceal torsion have been reported in the literature. Laparoscopy appears to be the most appropriate modality for diagnosis and treatment where the condition is suspected. To our knowledge this is the first case of appendiceal torsion in an adult causing right upper quadrant pain related to caecal malposition.